Young female participants show blunted placebo effects associated with blunted responses to a cue predicting a safe stimulus in the right dorsolateral prefrontal cortex - Iwama, Yudai; Takamoto, Kouichi; Hibi, Daisuke; Nishimaru, Hiroshi; Matsumoto, Jumpei; Setogawa, Tsuyoshi; Nishijo, Hisao (Frontiers in Neuroscience, 2022)
Discrimination of cues predicting non-nociceptive/nociceptive stimuli is essential for predicting whether a non-painful or painful stimulus will be administered and for eliciting placebo/nocebo (pain reduction/pain enhancement) effects. Dysfunction of the neural system involved in placebo effects has been implicated in the pathology of chronic pain, while female sex is one of the important risk factors for development of chronic pain in young adults. The dorsolateral prefrontal cortex (dl-PFC) is suggested to be involved in placebo effects and is sensitive to sex and age. In this study, to examine the neural mechanisms by which sex and age alter placebo and nocebo effects, we analyzed cerebral hemodynamic activities in the dl-PFC in different sex and age groups during a differential conditioning task. During the training session, two different sounds were followed by low- and high-intensity electrical shocks. In the following recording session, electrical shocks, the intensity of which was mismatched to the sounds, were occasionally administered to elicit placebo and nocebo effects. In young female participants, both placebo effects and hemodynamic responses to the conditioned sounds in the right dl-PFC were significantly lower than those in elderly female participants, while there were no age differences in male participants. The hemodynamic responses to the sound paired with the safe stimulus in the right dl-PFC were significantly correlated with placebo effects, except in the young female group. These results suggest that blunted placebo effects in the young female participants are ascribed to blunted responses to the sound associated with the safe stimulus in the right dl-PFC, and that sex- and age-related factors may alter the responsiveness of the right dl-PFC to associative cues predicting a safe stimulus.